Pathogenesis of IgE‐mediated food allergy and implications for future immunotherapeutics. Issue 7 (17th June 2021) - Ramsey, Nicole; Berin, M. Cecilia
Abstract: Our understanding of the immune basis of food allergy has grown rapidly in parallel with the development of new immune‐targeted interventions for the treatment of food allergy. Local tissue factors, including the composition of skin and gastrointestinal microbiota and production of Th2‐inducing cytokines (TSLP, IL‐33, and IL‐25) from barrier sites, have been shown not only to contribute to the development of food allergy, but also to act as effective targets for treatment in mice. Ongoing clinical trials are testing the targeting of these factors in human disease. There is a growing understanding of the contribution of IL‐13 to the induction of high‐affinity IgE and the need for continual T‐cell help in the maintenance of long‐lived IgE. This provides a strong rationale to test biologics targeting both IL‐4 and IL‐13 in the treatment of established food allergy. Various forms of allergen immunotherapy for food allergy have clearly shown that low specific IgE and elevated specific IgG4 are predictive of sustained treatment effect. Treatments that mimic that immune response, for example, lowering IgE, with monoclonal antibodies such as omalizumab, or administering allergen‐specific IgG, are in various stages of investigation. As we gain more opportunities to use immune‐modifying treatments for the treatment of food allergy, studies of the immune and clinical response to those interventions will continue to rapidly advance our understanding of the immune basis of food allergy and tolerance.